2022
DOI: 10.20473/cimrj.v3i2.38067
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Physical Activity and Fasting Blood Glucose in Patient With Type 2 Diabetes Mellitus

Abstract: Introduction: Diabetes Mellitus is a disease caused by an increase in blood glucose levels, which is an increase in levels at an abnormal level, or called hyperglycemia. Diabetes is a metabolic disease related to various factors such as physical activity, lifestyle, habits, diet, etc. Diabetes mellitus is classified as type 1 diabetes mellitus, type 2 diabetes mellitus, and gestational diabetes. Type 2 Diabetes Mellitus (T2DM) is caused by the body's inability to use insulin effectively (insulin resistance). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…15 It is important to highlight that while some evidence supports the use of random blood glucose of >200 mg/dL to define uncontrolled diabetes, the parameter can vary significantly based on activity level, dietary patterns, and actively consumed drugs. 16,17 The severity of DFU was found to have a significant association with both the ABI score and category. This finding is consistent with a previous study conducted at Wahidin Sudirohusodo Hospital, Makassar, which demonstrated a correlation between DFU severity and ABI.…”
Section: Discussionmentioning
confidence: 94%
“…15 It is important to highlight that while some evidence supports the use of random blood glucose of >200 mg/dL to define uncontrolled diabetes, the parameter can vary significantly based on activity level, dietary patterns, and actively consumed drugs. 16,17 The severity of DFU was found to have a significant association with both the ABI score and category. This finding is consistent with a previous study conducted at Wahidin Sudirohusodo Hospital, Makassar, which demonstrated a correlation between DFU severity and ABI.…”
Section: Discussionmentioning
confidence: 94%